Otros saberes: Collaborative research on indigenous and Afro-Descendant cultural politics - Hale, Charles R. Stephen, Lynn (2013)
research projects form the core of an initiative to bring together a diverse group of Afro-descendent and indigenous collaborations in Latin America with academics.